STANDAR KINERJA OPERASIONAL TERMINAL MUSTIKA ALAM LESTARI DI PELABUHAN TANJUNG PRIOK - Husni Hasan; I Made Indriani Darmiasih; Aswanti Setyawati (Institut Transportasi dan Logistik Trisakti, 2017)
The aim of the research is to be able to assess the activities undertaken by terminal operators because of the expected operational performance standard.. The problem of the research is that the operators or employees do not meet the expected standards of performance that have been set at Mustika Alam Lestari Terminal (MAL). This research used Developmental descriptive method. From the result of the study, there are four indicators that have not reached the standard of performance. First, waiting time (idle time) with standard 1 hour waiting time in 2016 which reached about 1.35 hours in which the results exceeds the standard set and declared by MALwhich is not good. Second, it is about ET: BT (Effective Time: Birthing Time) with a standard of 75% though in 2016 Mustika Alam Lestari reached about 73%. Third, the standard of 24 boxes Box/Crane/Hour of Mustika Alam Lestari in 2016 only reached an average of 19.63 boxes. The last is for delivery of containers with the standard set about 45 minutes but Mustika Alam Lestari terminal in 2016 reached 56.17 minutes for delivering the container. The sanctions or solutions made by the port authority as a regulator is to identify the performance of employees or operators that have not reached the expected standard and PT. Mustika Alam Lestari must provide an assessment or evaluation for improving employees performance.